Self-selection and the returns to geographic mobility: what can be learned from the German reunification experiment - Anzelika Zaiceva (Institute for the Study of Labor (IZA), 2006)
This paper investigates the causal effect of geographic mobility on income. The returns to German East-West migration and commuting are estimated, exploiting the structure of centrally planned economies and a natural experiment of German reunification for identification. I find that the migration premium is insignificantly different from zero, the returns for commuters equal to 40 per cent, and the local average treatment effects for compliers are insignificant. In addition, estimation results suggest no positive self-selection on unobservables for migrants, and some evidence of positive self-selection on unobservables for commuters.
urn:nbn:de:101:1-2008050264
Keywords: 330